The significance of Article 102 of the Treaty on the Functioning of the European Union in the Assessment of Distribution Contracts - Carvalho, Sónia de (2022)
In addition to article 101 of the TFEU, the abuse of a dominant position prohibited by article 102 of the TFEU is important for the analysis of the conformity of distribution contracts towards the UE Competition Law. The clauses of the distribution contracts often contain practices that are likely to represent an abuse of a dominant position, censured by article 102 of the TFEU. In fact, one of the types of conduct qualified by article 102, (b) of the TFEU as abuse of a dominant position is the limitation of "production, distribution or technical development to the prejudice of consumers", covering not only restrictive practices resulting from the dominant company's internal behavior, but also conducts which, by conditioning third parties, pursue such restrictive purposes. Exclusive purchase obligations and loyalty and fidelity discounts are of relevance in the distribution context. Tying also arises, frequently, in the context of distribution, and is frowned upon, according to article 102, (d) of the TFEU, if the company is using the dominant power in one market to obtain an advantage in another market, excluding rivals. Bundling and multi-product rebates, so common in distribution, are also practices that may constitute exclusionary conduct by dominant companies. The existence of abusive behavior regarding price, namely, the use of predatory pricing, excessive pricing or margin squeezes, prohibited by article 102, (a) of the TFEU is also common in distribution. The refusal to supply products and services is an abuse that may result from the clauses in distribution contracts and the way distribution networks are built, with the intention of excluding rivals, with particular emphasis when related markets are concerned. On the other hand, it can be one of the instruments to prevent parallel imports, segmenting the internal market, which will be severely censured by the CJEU. Vertical restrictions can also be considered an abuse of a dominant position if they correspond to unfair commercial conditions, expressly referred to in article 102, (a) of the TFEU as far as prices are concerned, and to a discriminatory treatment of commercial partners, through unequal conditions that put them at a disadvantage in competition, present in article 102, (c), which includes, for example, loyalty discounts. The European Union case law, in turn, has reflected the concern of the competition authorities in the analysis of abusive behavior of companies towards distributors and suppliers. In this paper, considering the relevance recognized by the Commission and European Union case law to exclusionary conduct in distribution and the correspondence of some of these abuses with vertical restraints, we will analyze exclusionary conduct, referring, whenever justified, exploitative abuses and market segmentation.